Information search behaviour among domestic tourists in Malaysia / Aimi Zarith Zuber - Zuber, Aimi Zarith (2013)
Information search is an act conducted in order to obtain values that an individual look for. The act usually starts from within, whereby one would retrieve the information from the memories. However, upon realizing lack of information, one would start enquire information from external sources. This is among a common case among travellers, who particularly look for information in order to plan their vacations. Among items that are most researched for includes their essential needs, such as meals, accommodation, transportation and more. In this increasingly competitive market place of tourism related products and services, it is important for the marketers to understand the information search behaviour of Malaysian tourists. This is crucial in order to formulate the best marketing strategies and to employ only the most effective media vehicles to achieve their marketing objectives. Thus, this study empirically investigates the common information sources most used by domestic tourists in Malaysia as well as how well these information sources usage influence consumers decision in purchasing travel related items. It was discovered that both internet and consultation with friends and family are dominating tourists’ choice in information seeking. However, travel brochures and travel guidebooks are found to have greater influence in purchase decision made by tourists. Thus, it is important for marketers to strategies their choice of media vehicle accordingly in order to ensure their market objective is achieved.